Development of Agricultural Non‐Point Source Pollution Reduction Measures in Korea†. (17th April 2016) - Cho, Moonsoo; Jang, Taeil; Jang, Jeong Ryeol; Yoon, Chun Gyeong
Abstract: The dramatic increase of non‐point source (NPS) pollutant loads in total pollutant loads necessitates urgent countermeasures against NPS pollution reduction. Point source treatment technology and measures for systematic agricultural NPS pollution reduction are needed, because agricultural NPS pollutants have been shown to have a stronger effect than other sources in the Saemangeum River Basin. Therefore, the present study, initiated in 2010 (a 7‐year project), focuses on the development of agricultural NPS pollution reduction measures in the Saemangeum River Basin. Farmers and residents still appear to have a very low awareness of agricultural NPS pollution in South Korea. Genuinely critical factors in reducing agricultural NPS pollution are efforts to develop best management practices (BMPs) that reduce NPS pollution and dissemination of the BMPs among residents, including farmers, so that the BMPs can be implemented. The tested BMPs showed a reduction effect of agricultural NPS pollution from paddy and upland areas. However, long‐term research results are needed to evaluate this effect, because no economic benefits through the BMPs application were observed. Based on the results of the present study, BMP manuals and environmental education teaching materials have been developed for the farmers. In addition, systematization of support for dissemination of BMP and participation of farmers has been promoted. Copyright © 2016 John Wiley & Sons, Ltd.